RESERVOIR QUALITY EVOLUTION OF UPPER CARBONIFEROUS (WESTPHALIAN) TIGHT GAS SANDSTONES, LOWER SAXONY BASIN, NW GERMANY. (16th September 2019) - Becker, I.; Busch, B.; Koehrer, B.; Adelmann, D.; Hilgers, C.
Abstract : This paper investigates reservoir quality development in tight Upper Carboniferous fluvial sandstones (Westphalian C/D) in the Lower Saxony Basin, NW Germany. The study integrates data from three outcrops (Piesberg, Woitzel and Hüggel) in the south of the basin with that from two wells (Wells A and B) located at gas fields approximately 50 km to the north. Petrographic and petrophysical data are related to the diagenetic evolution of the sandstones and the burial and structural history of the Lower Saxony Basin. The outcrop and subsurface data sets are compared in order to investigate the factors controlling reservoir quality evolution. Upper Carboniferous fluvial sandstones from the Woitzel and Hüggel outcrops and from Wells A and B have similar matrix permeabilities (0.01 to 10 mD), but matrix porosities vary between Well A (average 6%), Well B (average 10%), Woitzel (average 15%), and Hüggel (average 19%). Permeability reduction during burial is related to the formation of clay mineral cement, which was mainly controlled by variations in both the palaeo‐climate and in the sandstones' depositional composition. Matrix porosity was controlled by local differences in burial history related to basin inversion tectonics. The greater amount of inversion‐related uplift at Well B (about 2.8 km) resulted in lower thermal exposure of the Westphalian sandstones at this location, which thus show higher matrix porosities than the sandstones at Well A which were uplifted by only about 1.2 km. Further increases in porosity in the outcrop sandstones may be related to the dissolution of carbonate cement during late‐stage uplift in near‐surface conditions. Upper Carboniferous fluvial sandstones from the Piesberg quarry show the poorest reservoir characteristics compared to the samples from the subsurface and the other outcrops, with matrix porosities averaging 6% and permeabilities <0.01 mD. Reservoir quality reduction was controlled by thermal anomalies associated with a large fault at the Piesberg quarry. By contrast, a few outliers in the sample data sets from Well B and the Piesberg quarry, which have permeabilities of more than 100 mD, show that faulting or natural fracturing may enhance reservoir quality within a particular area. Faults/fractures may act as potential migration pathways for leaching fluids, or may provide fracture‐permeability systems with production potential. Depositional setting, burial‐related diagenetic processes and structural characteristics in the Lower Saxony Basin need to be carefully evaluated in order to provide an improved understanding of the reservoir quality of the Upper Carboniferous sandstones.